Modelling of wood resin interaction - Nuruldiyanah, Kamarudin (2010)
There are 11 medium density fibreboard (MDF) and 11 particle board (PB) plants in Malaysia. The total production capacity is approx 2.5 million cubic ton per year. Wood based industries constitute fourth biggest export earnings for the country. Thermosetting resin such as Urea Formaldehyde (UF) and Phenol formaldehyde (PF) constitutes near about 50% of the cost of wood composites. Not many studies have been carried out to understand the behaviour of resin on wood fibre. Sometimes manufacturer’s spray resin more than required which is a waste of material and some time they spray less, which may cause low internal bonding and low modulus of rupture of wood composite. There is a need to develop better understanding, by means of experimental data and modelling. The present model studies the impact of various factors such as resin surface tension, diameter of wood pores, resin contact angle on the penetration rate of resin on the wood surface. The Matlab software is used for programming and running the simulations. The present model will help the wood composite industries to develop better understanding of wood-resin interaction and to optimize the parameters, to get the better bonding between wood fibres.